2020
DOI: 10.31661/gmj.v9i0.1592
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vitamin D Replacement on Patient with Subclinical Hypothyroidism: A Pilot Randomized Clinical Trial

Abstract: Background: Subclinical hypothyroidism (SCH) is characterized by an elevated Thyroid Stimulating Hormone (TSH) with a normal T4. The prevalence of Vitamin D deficiency in patients SCH is high. Some studies suggested that Vitamin D supplements could be reduced serum concentration of TSH so improve SCH and prevent overt hypothyroidism. This study aims to explore the effect of vitamin D replacement on subclinical hypothyroidism. Materials and Methods: Fifty-nine patients, diagnosed with both subclinical hypothyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Ahi et al's case-control study linked non-autoimmune hypothyroidism in adults to vitamin D de ciency, suggesting a potential underlying connection (20). Notably, Pezeshki et al's randomized clinical trial demonstrated that vitamin D supplementation signi cantly lowered TSH levels in adult patients with subclinical hypothyroidism and vitamin D de ciency (21). This aligns with our study's ndings and supports the potential bene t of supplementation in this population.…”
Section: Discussionsupporting
confidence: 90%
“…Ahi et al's case-control study linked non-autoimmune hypothyroidism in adults to vitamin D de ciency, suggesting a potential underlying connection (20). Notably, Pezeshki et al's randomized clinical trial demonstrated that vitamin D supplementation signi cantly lowered TSH levels in adult patients with subclinical hypothyroidism and vitamin D de ciency (21). This aligns with our study's ndings and supports the potential bene t of supplementation in this population.…”
Section: Discussionsupporting
confidence: 90%
“…Pezeshki et al conducted a pilot randomized clinical trial in 2020 to investigate the efficacy of vitamin D therapy on subclinical hypothyroidism. The researchers discovered that using vitamin D supplements significantly reduced TSH mean levels, emphasizing the need for screening and vitamin D treatment in subclinical hypothyroid individuals [ 99 ]. Musa et al observed that hypothyroid patients had significantly higher TSH and lower FT4 levels compared to healthy controls in a case-control study of 116 females with hypothyroidism in Saudi Arabia.…”
Section: Reviewmentioning
confidence: 99%
“…Table 1 gives details of some clinical studies showing the various associations between Vitamin D and thyroid [ 42 , 46 , 48 , 49 , 52 , 59 , 82 , 83 , 84 , 85 , 88 , 90 , 94 , 98 , 99 , 100 , 102 , 103 , 104 , 109 ], all of which are mentioned in this review.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited studies discuss association between early hypothyroid disorders and vitamin D deficiency [9]. Giving vitamin D supplements may prevent form developing overt hypothyroidism [10,11].…”
mentioning
confidence: 99%